PENGARUH PROFITABILITAS, LEVERAGE DAN LABA AKUNTANSI TERHADAP RETURN SAHAM: (STUDI PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2021-2023) - Nur, Mufliha; Usman, Rudy; Muliati, Muliati; Parwati, Ni Made Suwitri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study was conducted to investigate the effect of profitability, leverage, and accounting profit on stock returns in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Methods: Profitability is represented by Return on Assets (ROA), leverage is measured by the Debt to Equity Ratio (DER), and accounting profit is proxied using profit growth. The research approach is quantitative, using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique processed with SmartPLS 4.0 software. The sample consisted of 21 energy companies selected through the purposive sampling method, resulting in 63 observations over three years. Results: The research findings show that profitability and leverage do not significantly affect stock returns, while accounting profit has a positive and significant effect. Simultaneously, the three variables explain 9.4% of the variability in stock returns, while the remainder is explained by other factors outside the model. These results indicate that accounting profit is one of the main indicators investors consider when assessing investment potential, while profitability and leverage are not yet reliable references in the energy sector. Conclusion and suggestion: These results indicate that accounting profit is one of the main indicators investors consider when assessing investment potential, while profitability and leverage are not yet reliable references in the energy sector. Since this study only focuses on internal company variables, it is recommended that subsequent studies consider external factors such as interest rates, inflation, exchange rates, and market perceptions. Further research can also use a longer time span and different analytical approaches to obtain more in-depth and relevant results in generalization.